The view from Saturday - Konigsburg, E. L. (New York, N.Y. Alladin Paperbacks, 1996)
Four students, with their own individual stories, develop a special bond and attract the attention of their teacher, a paraplegic, who chooses them to represent their sixth-grade class in the Academic Bowl competition.
Keywords: Teacher-student relationships -- Fiction; Friendship -- Fiction; Schools -- Fiction; Contests -- Fiction; People with disabilities -- Fiction